Sex differences in mortality and hospitalization in heart failure with preserved and mid-range ejection fraction: a systematic review and meta-analysis of cohort studies - Deng, You; Zhang, Jun; Ling, Jitao; Hu, Qingwen; Song, Tianggang; Xu, Yi; Liu, Menglu; Wu, Yuting; Mei, Kaibo; Chen, Jiawei; Zhao, Huilei; Liu, Xiao (Frontiers in Cardiovascular Medicine, 2024)
The influence of sex on the prognosis of heart failure with preserved or intermediate ejection fraction (HFpEF and HFmrEF) remains uncertain.Our objective was to investigate whether sex differences impact the prognosis of patients with HFpEF and HFmrEF. We conducted a comprehensive search of three databases (PubMed, the Cochrane Library, and Embase) to identify sex-related prognostic cohort studies focusing on HFpEF and HFmrEF. Risk estimates were synthesized using the random effects model. Our analysis included 14 cohorts comprising 41,508 HFpEF patients (44.65% males) and 10,692 HFmrEF patients (61.79% males).Among HFpEF patients, men exhibited a significantly higher likelihood of all-cause mortality (13 studies; hazard ratio (HR): 1.24, 95% confidence interval (CI): 1.15 to 1.33) and cardiovascular disease (CVD) mortality (5 studies; HR: 1.22, 95% CI: 1.14 to 1.31) compared to women, although no difference was observed in HF admissions (6 studies; HR: 1.01, 95% CI: 0.89 to 1.14). Among HFmrEF patients, men had a notably higher risk of all-cause mortality (3 studies; HR: 1.21, 95% CI: 1.12 to 1.31), but no significant differences were found in cardiovascular (CV) mortality (3 studies; HR: 1.17, 95% CI: 0.90 to 1.53) and HF admissions (3 studies; HR:1.06, 95% CI: 0.98 to 1.15). The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) assessment indicated moderate certainty for all-cause mortality, CV mortality, and HF 4 admission in patients with HFpEF and HFmrEF. In summary, male patients with HFpEF and HFmrEF may have a more unfavorable prognosis.